Short coupled Torsade de pointes with myocardial injury: A possible sequela of myocarditis - Marume, Kyohei (J Cardiol Cases, 2018)
A 44-year-old woman with previous myocarditis underwent several syncopal events due to self-terminated ventricular fibrillation (VF) with hypokalemia. Electrocardiogram showed a normal QT duration and premature ventricular contraction with a short coupling interval (280 ms), and the R-on-T phenomenon induced Torsade de pointes (TdP) that deteriorated into VF, a condition known as short coupled TdP (ScTdP). Cardiac magnetic resonance imaging showed left ventricular dilatation and diffuse high T2 signal intensity, and endomyocardial biopsy exhibited a failing myocardium. This is a rare case of ScTdP accompanied by a failing myocardium. Some instances of ScTdP may be associated not only with an electrical disorder but also with a structural myocardial disorder. <Leaning Objective: Any cases with short coupled Torsade de pointes (ScTdP) have not reported structural disorders, and ScTdP has been categorized as an idiopathic arrhythmia. This is the first case of ScTdP accompanied by a failing myocardium, which was identified by cardiac magnetic resonance imaging and both light and electron microscopic examination. According to this case, some cases of ScTdP may be associated not only with electrical disorders, but also structural myocardial abnormalities.>